Discovering the potential of utilizing artificial intelligence in tax procedures : AI-powered artifact as a knowledge creation instrument - Koivula, Karri Juha (My University, 2022)
Artificial intelligence, machine learning, and deep learning have become ubiquitous concepts. Interest in their utilization opportunities in many sectors has exponentially grown during recent decades partly due to the exponential growth of computer power and the increased availability of data, allowing for more powerful and sophisticated information technology solutions. Technological maturity has lowered the threshold, and various open-source libraries and active communities enable the utilization of algorithms such as neural networks in practice. This thesis set out to find whether deep learning algorithms could be utilized in a value-adding way in the procedure for limited liability companies responsible for handling tax claims in the case organization the Finnish Tax Administration. Additionally, the creation and deployment of artificial intelligence solutions should consider legal and ethical manners as restrictive key concerns. The research was carried out according to the action design research method in which the focus of the research is concurrently building a suitable artifact for the organization and learning (design principles) from the creation and intervention itself. The research method was chosen due to its inclination towards authenticity in the organization and organizational centricity. As a result, the project team consisting of three members created two functional artifacts: one based on neural networks and another based on self-organizing maps. The case organization provided data fueling the deep learning algorithms. Data consisted of financial information of anonymous limited liability companies in Finland. The artifacts were limited to function only as knowledge creation instruments due to legal and ethical limitations present in the context. Knowledge creation in this research context refers to the artifact's ability to identify customers not returning (defaulting) their income tax returns from others. The created artifacts functioned sufficiently, and their ability to identify defaulting customers from others was promising. Results suggest that it is recommendable to approach problems with more than one artifact solution, and focused roles in the project team are recommended. Artificial intelligence-based artifacts are seen as value-adding since the knowledge created by them can potentially save time, liberate resources and expedite processes. However, finalized artifacts were not created, and testing was limited to a simulated environment. The design principles that emerged from the artifact creation focused on addressing the legal and ethical challenges associated with artificial intelligence in taxation to secure sustainable artifact creation and usage. Design principles were divided into three levels: trustworthiness through accuracy, legal and ethical restrictions and limitations of use, and justification of use. An organization-defined performance threshold needs to be reached by an artifact. An artifact must be transparent and regulated to fulfill context-specified legal and ethical limitations. Lastly, a preliminary inspection of artificial intelligence usage in a case organization is required. Consequently, the preliminary results of this research should be validated by applying the concept in a case organization, followed by an analysis of the results in an end-user setting. Tekoäly, koneoppiminen ja syväoppiminen ovat muodostuneet kaikkialla läsnäoleviksi käsitteiksi. Kiinnostus niiden hyödyntämispotentiaaliin monilla toimialoilla on kasvanut viimeisten vuosikymmenten aikana. Laskentatehon ja saatavilla olevan tiedon eksponentiaalinen kasvu mahdollistavat tehokkaampien ja monimutkaisempien ratkaisujen luomisen. Teknologian maturiteetin kypsyminen on laskenut kynnystä ja avoimet ohjelmistokirjastot sekä aktiiviset yhteisöt mahdollistavat neuroverkkojen kaltaisten algoritmien hyödyntämisen käytännössä. Tämän opinnäytetyön tarkoitus oli tutkia tuottaako syväoppimisalgoritmien hyödyntäminen lisäarvoa osakeyhtiöiden verotuksen oikaisumenettelyssä Verohallinnossa. Lainmukaisten ja eettisten tekoälysovellusten luominen ja käyttöönotto tunnistettiin rajoittavaksi ja keskeiseksi tekijäksi. Tutkimus toteutettiin toiminnan suunnittelututkimuksen mukaisesti, jossa on tarkoitus samanaikaisesti luoda kohdeorganisaation soveltuva artefakti sekä oppia (suunnitteluperiaatteet) artefaktin luomisesta ja interventiosta organisaatioon. Tutkimusmenetelmä valittiin sen organisaatiokeskeisyyden ja organisaatiokohtaisen aitouden vuoksi. Tutkimusmenetelmän soveltamisen seurauksena kolmehenkinen projektiryhmä loi kaksi toimivaa artefaktia, joista toinen pohjautui neuroverkkoihin ja toinen itseohjautuviin karttoihin. Kohdeorganisaatio toimitti syväoppimisalgoritmien tarvitseman datan. Data koostui tunnistamattomien suomalaisten osakeyhtiöiden taloustiedoista. Artefaktit oli rajattu toimimaan ainoastaan nk. tietoa tuottavina työkaluina johtuen lain ja etiikan rajoitteista. Tiedon tuottamisella tutkimuskontekstissa viitataan artefaktin kykyyn tunnistaa asiakkaita, jotka eivät täytä niiden tuloverotuksen veroilmoitusvelvollisuutta. Luodut artefaktit toimivat riittävällä tasolla. Niiden kyky tunnistaa haluttua asiakasryhmää oli lupaava. Tulosten perusteella on suositeltavaa lähestyä ongelmia luomalla useita erilaisia tekoälysovellutuksia. Lisäksi suositellaan kiinnittämään huomiota keskitettyihin rooleihin projektiryhmässä. Tekoälypohjaiset artefaktit nähdään lisäarvoa tuottavina. Niiden tuottaman tiedon perusteella on mahdollista säästää aikaa, vapauttaa resursseja ja nopeuttaa prosesseja. Viimeisteltyjä ja organisaatioon vapautettuja artefakteja ei luotu. Artefaktien luonnin ja testauksen perusteella syntyneet suunnitteluperiaatteet keskittyivät vastaamaan lain ja eettisyyden asettamiin rajoitteisiin, jotka liittyvät tekoälyn hyödyntämiseen verotuksessa. Näin on mahdollista varmistaa kestävä tapa luoda artefakteja ja ottaa niitä käyttöön. Suunnitteluperiaatteet jaettiin kolmeen tasoon: luottamus tarkkuuden kautta, lain ja eettisyyden luomat rajoitteet käytössä ja tekoälyn käytön perustelu. Artefaktin tulee ylittää organisaatiokohtainen kynnys suorituskyvylle. Artefaktin tulee olla läpinäkyvä ja säännelty, jotta se noudattaa kohdeympäristönsä rajoitteita. Ennakollinen tutkimus tekoälyn hyödyntämiskohteista organisaatiossa on kehoitettavaa. Tämän työn saavuttamat ennakolliset tulokset on suositeltavaa vahvistaa kohdeorganisaatiossa, jota seuraa tulosten analysointi loppukäyttäjien keskuudessa.
Keywords: tekoäly; koneoppiminen; neuroverkot; veroilmoitukset; fi=Tietojärjestelmätiede|en=Information Systems|; fi=Tietojärjestelmätieteen maisteriohjelma|en=Master’s Programme in Information Systems|; Digitaalinen liiketoiminnan kehittäminen